Seismic characterization of lava flow facies in the critical zone of the deccan traps using shear wave velocity models - Rashi Sharma; Rahul Dehiya; Sudipta Sarkar; Raymond Duraiswami (Scientific Reports)
Abstract The critical zone is the uppermost layer of Earth’s crust, where the geosphere, hydrosphere, atmosphere, and biosphere interact to sustain life. In continental flood basalt provinces, its structure and evolution remain poorly understood due to lithological complexities and variable weathering patterns. Geological and geophysical characterization of the subsurface is essential to unravel these factors. Despite advances in understanding basalt lava flow stratigraphy in the Deccan Volcanic Province (DVP), field-scale seismic velocity variations within these flows and their internal structure remain largely unknown. This study integrates seismic data with volcanological information to investigate weathering patterns in the uppermost 50 m of basalt lava flows around Pune city in the western DVP. Using the multi-channel analysis of surface waves technique, we estimate shear wave velocity variations across flow units and dykes. By co-analyzing seismic data with morphological variations across outcrops, we develop a field-scale velocity characterization across basalt lavas and dykes. Critical zone facies, identified and validated through outcrop studies, include soil, weathered bedrock with vesicular basalt, columnar-jointed lava cores, red bole, and intrusive dykes. An analysis of vegetation distribution, landscape morphology, and lithological variability provides insights into key weathering and erosional processes shaping the critical zone in this volcanic terrain.